FUNCTIONAL DELAYED ECHOLALIA: INSIGHTS FROM A MOVIE - Qonitah Nuri Humaira; Emy Sudarwati (Universitas Islam Sumatera Utara (UISU), 2021)
This study focuses on the analysis of functional delayed echolalia towards an autistic individual in Life, Animated documentary. The obtained data were derived from Owen Suskind's utterances and words in the aforementioned documentary, which the researchers manipulated and structured to fall into two categories of functional delayed echolalia. The study used qualitative descriptive method in analyzing the functional delayed echolalia of Owen Suskind using interactive and non-interactive functional categories of delayed echolalia theory proposed by Vicker (1999). The findings show that there are 8 (eight) out of 9 (nine) types of interactive delayed echolalia were discovered namely Turn taking, Verbal, Completion, Providing information, Labelling, Protest, Request, Calling and Affirmation. Meanwhile, the non- interactive delayed echolalia consists of three types namely non-focused, situation association, and rehearsal. The findings of this study are expected to give a positive impact on both readers who are dealing with children with autism who have echolalia. It will provide information on their language development in order to later determine the ideal method to handle them with care.